2017
DOI: 10.1093/cid/cix692
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of an Educational Antimicrobial Stewardship Program on Hospital-Acquired Candidemia and Multidrug-Resistant Bloodstream Infections: A Quasi-Experimental Study of Interrupted Time-Series Analysis

Abstract: Background The global crisis of bacterial resistance urges the scientific community to implement intervention programs in healthcare facilities to promote an appropriate use of antibiotics. However, the clinical benefits or the impact on resistance of these interventions has not been definitively proved. Methods We designed a quasi-experimental intervention study with an interrupted time-series analysis. A multidisciplinary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 27 publications
3
64
0
Order By: Relevance
“…Our study shows that this kind of intervention may have sustainable results even if the initial design and implementation occur in an outbreak setting. There are concerns that reduction in consumption of some particular classes of antibiotics can result in unintended increase in other classes with similar deleterious ecological effects, the so called "squeezing the balloon effect" [14,20,21]. In our study we also measured total consumption of antimicrobials and observed a significant decreasing trend in the intervened ward.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Our study shows that this kind of intervention may have sustainable results even if the initial design and implementation occur in an outbreak setting. There are concerns that reduction in consumption of some particular classes of antibiotics can result in unintended increase in other classes with similar deleterious ecological effects, the so called "squeezing the balloon effect" [14,20,21]. In our study we also measured total consumption of antimicrobials and observed a significant decreasing trend in the intervened ward.…”
Section: Discussionmentioning
confidence: 55%
“…In this kind of setting usually several interventions are put in place to control the outbreak as rapidly as possible and because AMS effects in terms of resistance are expected on the long run it may be harder to convince healthcare providers of its benefit. Also there are reports that AMS interventions effects usually fade with time with few studies reporting results beyond 24 months [3,14] and the ones implemented during outbreak settings seem to be specially difficult to sustain once the outbreak is controlled [3]. Our study shows that this kind of intervention may have sustainable results even if the initial design and implementation occur in an outbreak setting.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations